Systemic Toxic Reaction Due Bee Stings in Dogs - Machado, Mizael; de Souza, Davi Emanuel Ribeiro; Landi, Marina Frota de Albuquerque; Wilson, Taís Meziara; Honorato, Sandy Menezes; Beccon, Camila Fagundes; de Castro, Márcio Botelho (Acta Scientiae Veterinariae, 2018)
Background: Toxic reactions due bee stings in human, companion animals, food animals and wild animals are sporadically reported. Accidents involving bees have been occurring in urban and rural areas since 1956, when African bees were introduced in Brazil, forming populations of aggressive hybrid Africanized bees. Their sting cause local and systemic reactions, which include dermatologic reactions, anaphylactic reactions and toxic systemic reactions before death. The aim of this article is to describe the clinical and pathological aspects of the toxic systemic reactions of two dogs that suffered a massive bee attack in the Federal District, Brazil. Cases: A 8-year-old female Brazilian mastiff, and one female 6-year-old Belgian shepherd were locked in the kennel when they suffered a massive bee attack. The dogs presented ‘apathy, congested mucous membranes, dyspnea, epistaxis, hemoglobinuria, icterus (one of them) and convulsions. Clinical pathology results showed a strong hemolyzed plasma, azotemia, leukocytosis with neutrophilia and monocytosis. Both animals were euthanized due to their critical conditions. At necropsy the dogs showed severe subcutaneous edema in the face, moderate congestion of mucous membranes, hematochezia and hematuria. Both dogs presented kidneys dark brown to blackened colored, urinary bladder replete with dark red fluid, lungs severely congested, intestines with severe mural edema and hyperemia containing bloody fecal matter inside, and the liver of one of the dog moderately icteric. The main histologic findings were the moderate diffuse degeneration of the kidney tubular epithelium with small focal areas of necrosis, countless casts of hemoglobin, granular and hyaline casts inside the renal tubules. The skin affected showed stingers inserted, dissociation of the collagen fibers by edema and multifocal areas of hemorrhage, neutrophils and eosinophils, and the muscular tissue underneath had intense necrosis, with hyalinization and moderate multifocal fragmentation of myocytes. Discussion: Africanized bees are well established in rural areas and can adapt to urban areas and, given their marked aggressiveness, cause accidents with animals and humans. Clinical and hematological changes presented by dogs in the DF are similar to those previously reported in this species, which are usually observed in hemolytic anemias and tissue damage caused by the acute inflammatory response due multiple bee stings. Nephrosis can be considered one of the most important toxic effects, due severe intravascular hemolytic disturbance and rhabdomyolysis, along with acute renal failure caused by the toxin components in the tubules and the toxic-isquemic condition, causing azotemia. Hemolysin proteins such as fosfolipase A and melitina cause rhabdomyolysis, intravascular hemolysis, and hemoglobinemia, which trigger the process of diffuse nephrosis and acute renal failure. The main pathologic changes were observed in the kidneys and skin of the dogs in the DF and were similar to that previously reported in dogs with severe bee stings. The count of inserted bee stingers in the skin and history is considered important to establish a presumptive diagnosis and initiate immediate treatment for the affected animals. The epidemiologic and clinical-pathologic findings presented in these cases are similar to those observed in humans who had suffered systemic toxicity by bee stings and aggravates the general condition of the patient even leading to death. Based on these findings, it was possible to establish the diagnosis of systemic toxic reaction in dogs secondary to poisoning by Africanized bee stings. Keywords: poisonous arthropods, Africanized bees, systemic toxic reaction, toxicology.